A novel Stewart-type parallel mechanism with topological reconfiguration: Design, kinematics and stiffness evaluation. (August 2021) - You, Jingjing; Xi, Fengfeng; Shen, Huiping; Wang, Jieyu; Yang, Xiaolong
Highlights: The stiffness of parallel mechanisms can be enhanced by topological reconfiguration. We design a novel reconfigurable parallel mechanism with zero coupling-degree. A dimensionally homogeneous overall rotational stiffness matrix is deduced. The optimization criterion equation for the stiffness enhancement is derived. The path planning model for the full mobility motion control is formulated. Abstract: A new approach is put forward to enhance the stiffness of parallel mechanisms by topological reconfiguration. First, a novel 6-DOF Stewart-type parallel mechanism is designed and analyzed. This mechanism can be reconfigured into three topological configurations, each permitting one rotational motion by means of lockable prismatic joints. Then, an overall rotational stiffness matrix is analytically deduced by relating the external loads exerted on the end-effector to the magnitude of the induced micro-angular displacements. It is proved that the minimum eigenvalue of this matrix can serve as a stiffness index of the parallel mechanism. Subsequently, an optimization objective function is developed for stiffness enhancement through topological reconfiguration, and a singularity-free path planning model for full mobility motion control is formulated. Finally, numerical simulations are provided to compare the stiffness index values of the unlocked and locked mechanisms. The results show that the stiffness of the latter is substantially larger than that of the former, thereby demonstrating the effectiveness of the proposed approach.